THE EFFECT OF RETURN ON ASSET, EARNING PER SHARE, FREE CASHFLOW AND DEBT TO EQUITY RATIO ON COMPANY VALUE WITH DIVIDEND POLICY AS INTERVENING VARIABLES (STUDY THE CASE OF REGISTERED MINING COMPANIES IN INDONESIA STOCK EXCHANGE) YEAR 2016-2020 - Permata Hati Hulu, Intan; Yahya, Idhar; Absah, Yeni (CV. Radja Publika, 2022)
This study aims to determine how the effect of Return On Assets, Earning Per Share, Free Cash Flow and Debt to Equity Ratio on the value of mining companies listed on the Indonesia Stock Exchange. In addition, this study also aims to determine whether dividend policy can be used as an intervening variable in this research model.This type of research is quantitative research. The population in this study are mining companies listed on the Indonesia Stock Exchange in 2016-2020. The sample in this study was determined using a purpose sampling technique. The number of observations in this study amounted to 45 data. In this study, the data analysis method used to test the effect of Return On Assets (ROA), Earning Per Share (EPS), Free Cash Flow, and Debt to Equity Ratio (DER)) on firm value by using software eviews.The results in this study indicate that Return On Assets (ROA), Earning Per Share (EPS), FCF, and Debt to Equty Ratio (DER) have no effect on firm value. Return on Assets (ROA) and Earning Per Share (EPS), have an effect on dividend policy, while FCF and DER have no effect on dividend policy. Dividend policy variables cannot mediate On Asset (ROA), Earning Per Share (EPS), FCF, and Debt to Equty Ratio (DER) to Firm Value.